Counseling Using Booklet Media And Simulation Of Food Handler Hygiene During The Covid-19 Endemic: Counseling Using Booklet Media And Simulation Of Food Handler Hygiene During The Covid-19 Endemic Konseling Menggunakan Media Buklet Dan Simulasi Kebersihan Penanganan Makanan Pada Masa Endemik Covid-19 - Kaluku, Khartini; Sari, Martha Puspita (Universitas Lancang Kuning, 2024)
SARS-Cov-2 is a new virus that causes respiratory diseases that can cause respiratory system disorders, acute pneumonia, and death. The COVID-19 endemic continues to show positive things towards the endemic. The step to prevent COVID-19 is to convey information to the public regarding the prevention of COVID-19. The importance of hygiene in food handlers so that safe food is served is the focus of the implementation of Community Service activities. Hygiene implementation behavior is supported by nutritional knowledge, attitudes or behavior of the handler starting from the preparation, cleaning, processing, transportation to serving to consumers. Booklets as a health education communication medium can increase the average knowledge and nutritional attitudes of the handler towards the implementation of institutional food hygiene. Community service through a community partnership program was carried out through counseling and simulations using booklet media in Batu Merah Village as an effort to implement food handler hygiene during the Covid-19 endemic period. The counseling participants were food handlers at the Batu Merah Village Institutional Food Site, totaling 50 people. This activity adds insight into the thinking of participants regarding the application of hygiene, and through simulations the handlers can realize hygiene practices and be applied every day at food service institutions.